Projeto de drenagem superficial: estudo de caso: rodovia classe III na cidade de Tucuruí – Pa - NOVAES, Luiz Henrique Nunes (2023)
Drainage is an essential item in the infrastructure of highways, as in addition to extending its useful life, it promotes the protection of containment works, reduces deterioration in the surroundings and reduces expenses with road conservation. Therefore, an effective drainage system assists in the safe removal of water and prevents its accumulation both on the track platform and its surroundings. Therefore, the objective of this work is to carry out the most economical surface drainage project for a stretch of highway to be built in Tucuruí - PA. For this, the dimensioning of the 1st line drainage (gutters and ditches) was carried out through the comparison between the calculated critical length and the actual extension of the section - with subsequent choice of the most economical elements that could technically meet the project -, followed by the dimensioning of the 2nd line drainage (waterfalls and culverts) by determining the dimensions of each element, considering the actual flows calculated for the gutters. The main results found were: The standard section adopted for the gutters was STC-03, with a minimum critical length of 545.17m (curved section in cut) and a maximum of 1236.12m (straight section in embankment); The standard section adopted for the cutting protection ditches was the VPC-04, with the highest flow rate of 0.39m³/s occurring in the V19 ditch; The standard section adopted for the landfill protection ditches was VPA-04, with the highest flow rate of 0.23m³/s occurring in ditch V18; The water descent chosen was the DCD-04 type, with a width of 0.80 m and a height of 1.00 m; The graded culverts adopted were of the BSCC type, with a base and height of 1.50 m. Finally, it could be concluded that the project was successful from a technical and economic point of view, since it was possible to point out solutions that best met the project requests and, simultaneously, reduced material costs.